2016
DOI: 10.1051/matecconf/20168604023
|View full text |Cite
|
Sign up to set email alerts
|

Green sulfur-extended asphalt concrete: mix design of the complex binder

Abstract: Abstract. Using the ordinary sulfur extended asphalt leads to emission of toxic gases. The efficient method to prevent the emission is to use other admixtures as suppressors, but this requires the complication of the mix design scheme. In the present work we have extended the well known design method for the case of complex binder with arbitrary number of suppressors. The example of application of the proposed method is given. The results indicate that even for the relatively small amounts of suppressors it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The authors of works [ 1 , 2 , 3 , 4 , 5 , 6 ] have shown that the use of sulfur as a modifier for asphalt concrete is a promising direction, allowing the expansion of the temperature range of operation of asphalt concrete pavements in the area of high positive temperatures. In addition, in works [ 5 , 6 , 7 ] it is shown that the introduction of sulfur provides a decrease in the amount of bitumen in the asphalt concrete mixture, as well as a decrease in the temperature of preparation and laying The use of sulfur improves not only the operational properties of sulfur asphalt concrete (SEA) but also the technological properties of the mixture. Thus, in [ 8 ], the rheological properties of a bitumen-sulfur melt were investigated and it was shown that the introduction of sulfur significantly reduces the viscosity of such melts.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of works [ 1 , 2 , 3 , 4 , 5 , 6 ] have shown that the use of sulfur as a modifier for asphalt concrete is a promising direction, allowing the expansion of the temperature range of operation of asphalt concrete pavements in the area of high positive temperatures. In addition, in works [ 5 , 6 , 7 ] it is shown that the introduction of sulfur provides a decrease in the amount of bitumen in the asphalt concrete mixture, as well as a decrease in the temperature of preparation and laying The use of sulfur improves not only the operational properties of sulfur asphalt concrete (SEA) but also the technological properties of the mixture. Thus, in [ 8 ], the rheological properties of a bitumen-sulfur melt were investigated and it was shown that the introduction of sulfur significantly reduces the viscosity of such melts.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfur-extended asphalt is of improved physical, mechanical and operational properties. In particular, such asphalt is characterized by improved fatigue life under cyclic loads and increased resistance to rutting [5][6][7][8][9]. It is also resistant to the effects that are caused by various aqueous solutions and petrochemicals -gasoline and motor oils [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, such materials are characterized by high resistance to rutting, extended fatigue life and corrosion resistance [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introduction and Prior Workmentioning
confidence: 99%